A micro-power generation from rain shower utilizing PZT and PVDT piezoelectric transducer - Yaakub, Muhamad Faizal; Basar, Mohd Farriz; Yahaya, Muhammad Sharil; Mohd Noh, Faridah Hanim; Kamarudin, Hanis Zafirah (Asian Research Publishing Network (ARPN), 2017)
As the fossil resources are at risk of extinction, many efforts are being introduced to produce electrical energy. Micro-electrification by utilizing the energy from vibration has become an alternative way to generate electricity. It is through a device with sub-micron-scale dimension sub-micron-scale dimension. This work focus to generate electricity with the utilization of the off-the-shelf piezoelectric transducers; Polyvinylidene Fluoride (PVDF) and Lead Zirconate Titanate (PZT) under different rain shower density. With the three different flow rate of an artificial rain shower, it is able to generate maximum power of 2.4x10-6Watt and 27x10-6Watt for PVDF and PZT, respectively. However, the energy is significantly influenced by the rectifier circuit. This paper presents the performance of the power generation from raindrop using piezoelectric transducers available in the open market.